Favorable intermediate risk prostate cancer with biopsy Gleason score of 6 - Oh, Jong Jin (BMC Urol, 2021)
BACKGROUND: To identify potential prognostic factors among patients with favorable intermediate risk prostate cancer with a biopsy Gleason score 6. METHODS: From 2003 to 2019, favorable intermediate risk patients who underwent radical prostatectomy were included in this study. All patients were evaluated preoperatively with MRI. Using PI-RADS scores, patients were divided into two groups, and clinic-pathological outcomes were compared. The impact of preoperative factors on significant pathologic Gleason score upgrading (≥ 4 + 3) and biochemical recurrence were assessed via multivariate analysis. Subgroup analysis was performed in patients with PI-RADS ≤ 2. RESULTS: Among the 239 patients, 116 (48.5%) were MRI-negative (PI-RADS ≤ 3) and 123 (51.5%) were MRI-positive (PI-RADS > 3). Six patients in the MRI-negative group (5.2%) were characterized as requiring significant pathologic Gleason score upgrading compared with 34 patients (27.6%) in the MRI-positive group (p < 0.001). PI-RADS score was shown to be a significant predictor of significant pathologic Gleason score upgrading (OR = 6.246, p < 0.001) and biochemical recurrence (HR = 2.595, p = 0.043). 10-years biochemical recurrence-free survival was estimated to be 84.4% and 72.6% in the MRI-negative and MRI-positive groups (p = 0.035). In the 79 patients with PI-RADS ≤ 2, tumor length in biopsy cores was identified as a significant predictor of pathologic Gleason score (OR = 11.336, p = 0.014). CONCLUSIONS: Among the patients with favorable intermediate risk prostate cancer with a biopsy Gleason score 6, preoperative MRI was capable of predicting significant pathologic Gleason score upgrading and biochemical recurrence. Especially, the patients with PI-RADS ≤ 2 and low biopsy tumor length could be a potential candidate to active surveillance.